Predicting Millennials E-Loyalty Through Compatibility and Innovativeness on E-Commerce - I Putu Wahyu Dwinata JS; Made Pradnyan Permana Usadi; I Wayan Sucipta Wibawa (AIBPM Publisher, 2022)
Millennials have dominated the use of e-commerce. They tend to have characters with lower levels of loyalty to products or services. This will be a problem if e-commerce companies are unable to read the personal characteristics of its users. Millennials users are known to have innovativeness which is explained in their enjoyment of learning new systems. This perception also reflected through their assumptions about ease of use and usefulness of an e-commerce platforms. This study aims to examine the effect of perceived compatibility and perceived innovativeness to e-loyalty through perceived ease of use and perceived usefulness on millennials e-commerce users. Data are collected from 217 millennial customerâ€™s using purposive sampling method. Path analysis were done using SPSS Statistics 22. The results revealed both of perceived compatibility and perceived innovativeness affected e-loyalty significantly through perceived usefulness. The results of this study shows that ease of use does not necessarily make users loyal, because there are several other important factors such as price, promotion, service quality.Â Keywords: Compatibility, E-Loyalty, Innovativeness, Technology Acceptance Model